The current state of naive human pluripotency - Dodsworth, B; Flynn, R; Cowley, S (Wiley, 2015)
Naïve or ground state pluripotency is a cellular state in vitro which resembles cells of the preimplantation epiblast in vivo. This state was first observed in mouse embryonic stem cells and is characterized by high rates of proliferation, the ability to differentiate widely, and global hypomethylation. Human pluripotent stem cells (hPSCs) correspond to a later or "primed" stage of embryonic development. The conversion of hPSCs to a naïve state is desirable as their features should facilitate techniques such as gene editing and more efficient differentiation. Here we review protocols which now allow derivation of naïve human pluripotent stem cells by transgene expression or the use of media formulations containing inhibitors and growth factors and correlate this with pathways involved. Maintenance of these ground state cells is possible using a combination of basic fibroblast growth factor and human leukemia inhibitory factor together with dual inhibition of glycogen synthase kinase 3 beta, and mitogen-activated protein kinase kinase (MEK). Close similarity between the ground state hPSC and the in vivo preimplantation epiblast have been shown both by demonstrating similar upregulation of endogenous retroviruses and correlation of global RNA-seq data. This suggests that the human naïve state is not an in vitro artifact.